Análise da exposição ocupacional ao ruído em funcionárias de casas lotéricas localizadas na cidade de Curitiba/PR - Leutz, Amanda (2013)
This academic work has the objective to quantify the noise level for the lottery shop workers, for this study was used a dosimeter equipment from Instrutherm, model DOS-500 (device not calibrated), scheduled according to the settings of NR-15. This measurement was made in three lottery shops of Curitiba/PR and in each lottery shop was chosen one worker for the analysis. The results show that the noise level is acceptable according with NR-15. When the results are compared with other normative, NR-17, IAAN e WHO, the noise level beyond the acceptable level for job environment, what can cause occupational problems as: stress, changes in sleep and concentration, gastritis, and others changes. This is worrying when is an environment that requires attention, because the activities involve calculation and handling money.